Effects of Low-Calorie Nutrition Claim on Consumption of Packaged Food in China: An Application of the Model of Consumer Behavior - Huang, Zeying; Li, Haijun; Wang, Pei; Huang, Jiazhang (Frontiers in Psychology, 2022)
China is confronted with serious problems of overweight and obesity amongst the general population, resulting in a growing demand for low-calorie foods. Nutrition claim is a nutrition labeling, which informs consumers of food nutritional properties. More and more packaged products in China have been labeled with low calorie since nutrition claim was officially implemented in 2007. Nevertheless, little is known about the possible impact of nutrition claim on the consumption of low calorie products. Current study sought to fill this gap by applying model of consumer behavior through a nationally representative online survey. The findings revealed that nutrition claim could significantly affect low-calorie products consumption behavior. Specifically, consumer psychology firstly affected by marketing stimulus on low-calorie products, then influenced consumer decision making and lastly consumer responses. Despite consumer psychology and consumer decision making played bigger role, consumers were susceptible to target marketing strategies of foods with low-calorie claim. Therefore, it is encouraged that manufacturers adopt proper marketing techniques of products with low-calorie claim.